Differential levels of IFNα subtypes in autoimmunity and viral infection. (August 2021) - Bondet, Vincent; Rodero, Mathieu P.; Posseme, Céline; Bost, Pierre; Decalf, Jérémie; Haljasmägi, Liis; Bekaddour, Nassima; Rice, Gillian I.; Upasani, Vinit; Herbeuval, Jean-Philippe; Reynolds, John A.; Briggs, Tracy A.; et al.
Highlights: Development of digital ELISA with high attomolar sensitivity for the IFNα2 subtype. Identified different IFNα subtype ratios in viral infection and autoimmune patients. Subgroup of autoimmune patients had high IFNα2 but low pan-IFNα protein measurements. In this sub group of patients IFNα2 protein did not reflect its biological activity. Phenotype was partly explained by anti-IFNα auto-antibodies in a subset of patients. Abstract: Type I interferons are essential for host response to viral infections, while dysregulation of their response can result in autoinflammation or autoimmunity. Among IFNα (alpha) responses, 13 subtypes exist that signal through the same receptor, but have been reported to have different effector functions. However, the lack of available tools for discriminating these closely related subtypes, in particular at the protein level, has restricted the study of their differential roles in disease. We developed a digital ELISA with specificity and high sensitivity for the IFNα2 subtype. Application of this assay, in parallel with our previously described pan-IFNα assay, allowed us to study different IFNα protein responses following cellular stimulation and in diverse patient cohorts. We observed different ratios of IFNα protein responses between viral infection and autoimmune patients. This analysis also revealed a small percentage of autoimmune patients with high IFNα2 protein measurements but low pan-IFNα measurements. Correlation with an ISG score and functional activity showed that in this small sub group of patients, IFNα2 protein measurements did not reflect its biological activity. This unusual phenotype was partly explained by the presence of anti-IFNα auto-antibodies in a subset of autoimmune patients. This study reports ultrasensitive assays for the study of IFNα proteins in patient samples and highlights the insights that can be obtained from the use of multiple phenotypic readouts in translational and clinical studies.